Fate of Microplastics in Deep Gravel Riverbeds: Evidence for Direct Transfer from River Water to Groundwater - Marco Pittroff; Matthias Munz; Bernhard Valenti; Constantin Loui; Hermann-Josef Lensing (Microplastics, 2025)
Riverbed sediments act as potential retention reservoirs or transport corridors for microplastic particles (MPs) from river water to groundwater. Vertical concentration profiles of MPs, together with river water and groundwater analysis, provide insight into their fate and transport behavior in freshwater systems. However, such data remain scarce. This study provides a depth-specific analysis of MPs ≥ 100 µm (abundance, type, and size) in gravelly riverbed sediments down to 200 cm, along with river water and groundwater analysis. Three sediment freeze cores were collected from the Alpine Rhine, a channelized mountain stream with high flow velocities and permanent losing stream conditions. The average MP abundance in the riverbed was 3.1 ± 2.3 MP/kg (100–929 µm); in the river, 92 ± 5 MP/m3 (112–822 µm); and in the groundwater, 111 ± 6 MP/m3 (112–676 µm). The dominant polymer types in the riverbed were polypropylene (PP), polyvinyl chloride (PVC), and polyethylene terephthalate (PET) (>70%), while polyamide (PA) dominated in the river water (56%) and the groundwater (76%). The comparable MP concentration, particle sizes, and polymer types between river water and groundwater, as well as the vertical MP concentration profiles, indicate that even large MPs up to 676 µm are transported from river water to groundwater without significant retention in the gravel sediment.